Pengaruh Manajemen Modal Kerja dan Rasio Keuangan terhadap Profitabilitas pada Industri Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019 - Anggraini, Oktavia Nur; Febriyanto, Febriyanto (Jurnal Manajemen DIVERSIFIKASI, 2021)
This study aims to determine the effect of working capital management and financial ratios on profitability. Working capital management used in this research is cash turnover, accounts receivable turnover. The financial ratios in this study are proxied by the current ratio. Profitability as the dependent variable is proxied by ROA. The research design used by researchers in this study used a quantitative approach. The object of this research is companies that are included in various industrial sector companies that are classified as manufacturing industries that are listed on the Indonesia Stock Exchange in 2017-2019. The population in this study were 51 companies officially registered on the IDX. The sampling technique used was purposive sampling. In order to obtain a sample of 17 companies that meet the required sample characteristics. Based on the results of the study shows that the cash turnover variable has a positive and insignificant effect, receivables turnover has a significant negative effect. Meanwhile, the current ratio has a positive and significant effect on profitability.